ANALISIS PENGEMBANGAN WILAYAH MELALUI PENDEKATAN KLASTER INDUSTRI STUDI KASUS PERIKANAN LAUT KABUPATEN SUKABUMI, PROPINSI JAWA BARAT - H.Hutahaean, Erwin
ABSTRACT: The existence a region in international economic context, driven by their ability to create basic competence to survive in inter region competition. In odder to defence their existence in competition, pursuit paradigm changes in regional development strategy. Economic development that only chase high growth with depend on comparative advantage such of plenty natural resources and low labour cost cannot be obtained anymore. The main problem in regional development are making a integrated policy. The choices of sector and commodity development oftenly disregard their linkages with another sector/commodity. According to Michael Porter (1990), the correct industrial development approach for Indonesia which in decentralization and global competition atmosphere are industrial cluster. Even though have a great natural resources supported, the Sukabumi regency marine fish cluster has not growth in the few last year, mainly in market improvement, production process improvement and product improvement. Base on Industrial cluster analysis, this research recommended several policy to improve the Sukabumi regency marine fish Master.